Judaic religion in the Second Temple period : belief and practice from the Exile to Yavneh - Grabbe, Lester L. (Routledge, 2000)
This text focuses on a holistic interpretation of the Second Temple period (c.550 BC - 100 AD) and its importance for the nature of Jewish religion in later centuries. Topics examined include views on God, the temple and priesthood and messianism.